2014
DOI: 10.1590/s1517-83822014000300034
|View full text |Cite
|
Sign up to set email alerts
|

Depuration Times of Donax trunculus and Tapes decussatus

Abstract: The present study was performed to determine the depuration time and ability of Donax trunculus (Wedge Clam) and Tapes decussatus (Carpet Shell) contaminated with Escherichia coli, Salmonella enterica subsp. enterica serovar Typhimurium and Vibrio parahaemolyticus. Clams were contaminated with each bacterium at the level of 7.0 – 8.0 Log10 cfu/g. After contamination, clams were analyzed every 3 h in the first 24 h time period and every 6 h until the 72nd hour. During the depuration process of both clams, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…in ozonated and naturally contaminated oysters or bivalves are available. Çolakolu et al (2014) reported mean initial Salmonella typhimurium loads (8.8 ± 0.4 and 6.4 ± 0.6 log 10 CFU/g) in Donax trunculus and Tapes decussatus , respectively. Salmonella typhimurium was the first strain excreted from both clam species after 66 h of ozone depuration with an open-circuit (6 L/min) at 50 mg/h O 3 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…in ozonated and naturally contaminated oysters or bivalves are available. Çolakolu et al (2014) reported mean initial Salmonella typhimurium loads (8.8 ± 0.4 and 6.4 ± 0.6 log 10 CFU/g) in Donax trunculus and Tapes decussatus , respectively. Salmonella typhimurium was the first strain excreted from both clam species after 66 h of ozone depuration with an open-circuit (6 L/min) at 50 mg/h O 3 .…”
Section: Discussionmentioning
confidence: 96%
“… Croci et al (2002) reported that experimentally contaminated mussels ( Mytilus galloprovincialis ) showed a reduction of E. coli (42%) after 5 h, while V. cholerae O1 and V. parahaemolyticus declined by 1 log after 24 h depuration with 50 mg/h ozone, remaining almost constant for 44 h. Likewise, Meloni et al (2008) showed a decrease in E. coli counts after 8 h depuration, while naturally occurring Vibrios declined at a slower rate (6.7%). Çolakolu et al (2014) reported that E. coli and Salmonella enterica subsp. enterica serovar typhimurium were eliminated in 78 and 66 h, respectively, whereas V. parahaemolyticus was present after 72 h in clams ( Donax trunculus and Tapes decussatus ), depurated with 50 mg/h-ozone.…”
Section: Discussionmentioning
confidence: 99%